Localized reversal of the perpendicular velocity in Tore Supra ohmic, L-mode, limited plasmas. (6th March 2017) - Trier, E.; Hennequin, P.; Gürcan, Ö.D.; Sabot, R.; Bucalossi, J.; Guimarães-Filho, Z.O.; Bourdelle, C.; Clairet, F.; Falchetto, G.; Fenzi, C.; Garbet, X.; Maget, P.; et al.
Abstract: In Tore Supra plasmas, the perpendicular velocity measured by Doppler reflectometry was observed to reverse in a localized zone close to a normalized radius ̃0.5–0.6, changing from a negative value (corresponding to a negative radial electric field E r ) to a positive value ( E r > 0 ). This occurs in L-mode, ohmic plasmas with a negligible external momentum input, a non-circular limited cross-section, and an edge safety factor close to 3. This reversal is favoured by a decrease in the magnetic field, or an increase in density. It is accompanied by a characteristic behaviour of the MHD activity signal, whose amplitude decrease during a ramp-down of the edge safety factor as it approaches q a ∼ 3.1 –3.2. A m / n = 2/1 mode is involved in the mechanism causing these observations.